Is the untranslatability between languages ​​possible? Considerations around the Kuhn-Davidson debate (2009)
The article discusses the posibility or imposibility of partial failure of translatability between languages which have different systems of lexical categories. For that purpose we reformulate Kuhn's argument of not overlaping principle between taxonomic categories basing it on the thesis that every language requires from its speakers the acceptance of certain sentences (fixed points) in order to be qualified speakers. The necessity of not accepting sentences which are incompatible with those fixed points will prevent the possibility of translation.